Answer: The equation is
y = 5x/3 + 2
Step-by-step explanation:
represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
The slope is given as 5/3 and the point that it passes through is
(-3, -3)
To determine the intercept, we would substitute x = - 3, y = - 3 and m= 5/3 into y = mx + c. It becomes
- 3 = 5/3 × - 3 + c = - 5 + c
c = - 3 + 5 = 2
The equation becomes
y = 5x/3 + 2